PENGARUH STOCK SPLIT TERHADAP HARGA SAHAM, ABNORMAL RETURN, VOLUME PERDAGANGAN DAN RISIKO SISTEMATIS PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - M. Zukhruf Firdaus, (2023)
This research is quantitative research that aims to see whether there is an effect of stock split on stock price, abnormal return, trading volume and systematic risk by looking at whether there are differences in the period before and after the stock split. This study used a sample of 53 companies that conducted stock splits in the 2018- 2022 period. The data analysis used was Wilcoxon signed-ranks test using SPSS 29 tool. The results of this study show that (1) There is a difference in stock price before and after the stock split; (2) There is an abnormal difference in return before and after the stock split; (3) There is a difference in trading volume before and after the stock split; (4) There are systematic risk differences before and after the stock split.